Pengawasan Terintegrasi Terhadap Kampanye Prematur Petahana Dalam Pemilihan Kepala Daerah - Muhamad Saleh; Sahid Hadi (Badan Pengawas Pemilihan Umum, 2020)
This article is written on two objects of study. First, what are the conceptual, normative, and institutional problems in the supervision of the incumbent's premature campaign in a Local Election? Second, how is the idea of an integrated design to supervise the premature campaign of the incumbent? This normative research is conducted using a case, conceptual, and statutory approach. The finding of this study is that the premature campaign has not been strictly regulated by the Election Law. The absence of a strict regulation means that the incumbent's premature campaign can be interpreted using various regulations so that the ambiguity of the supervisory institution existed in this case. Therefore, integrated supervision is offered. Integrated supervision in this context provides a formal coordination forum among supervisory agencies, consisting of representatives from the supervision of the ethical regime, government, public services, law enforcement, with the Bawaslu as the coordinator.